2018
DOI: 10.3389/fpls.2018.01696
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Sand Burial and Wind Erosion on Regeneration and Growth of a Desert Clonal Shrub

Abstract: Sand burial and wind erosion caused by sand movement are common phenomena in desert environments, but the effects on clonal shrub have rarely been investigated. Here, we assessed how sand movements affect the population regeneration capacity of juvenile clonal fragments of the shrub Calligonum mongolicum growing in mobile desert sand dunes. We investigated the population status and natural regeneration capacity in three types of mobile dunes (heavy wind erosion, heavy sand burial and moderate sand burial). Clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
(72 reference statements)
1
10
0
Order By: Relevance
“…As expected, compared with the control condition, P n , C i and T r of all saplings decreased significantly in response to wind erosion (Table 2). The gas exchange reduction caused by wind erosion has been reported previously, such as Calligonum mongolicum (Fan et al, 2018), Rhododendron ferrugineum (Caldwell, 1970), and Averrhoa carambola (Marler and Zozor, 1992). We found that females always exhibited greater P n than did males under either control or wind erosion.…”
Section: B a Figuresupporting
confidence: 77%
See 2 more Smart Citations
“…As expected, compared with the control condition, P n , C i and T r of all saplings decreased significantly in response to wind erosion (Table 2). The gas exchange reduction caused by wind erosion has been reported previously, such as Calligonum mongolicum (Fan et al, 2018), Rhododendron ferrugineum (Caldwell, 1970), and Averrhoa carambola (Marler and Zozor, 1992). We found that females always exhibited greater P n than did males under either control or wind erosion.…”
Section: B a Figuresupporting
confidence: 77%
“…Previous studies have reported that morphological growth and biomass accumulation of plants are significantly inhibited under wind erosion environment (Yu et al, 2008;Li et al, 2010;Liu et al, 2014a). Photosynthesis, including net photosynthetic rate and chlorophyll fluorescence parameters, also shows similar trends (Fan et al, 2018). Adjustments in morphological and physiological characteristics constitute the important means by which plants increase their resistance and adaptability (Anten et al, 2005;Liao et al, 2020).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies have focused on its root ecology (Xu et al 2017b) and physiological responses to environmental disturbance ( e.g . sand burial and wind erosion) (Fan et al 2018; Wang et al 2019). However, available data on the responses of C. mongolicum seedlings to N deposition and drought are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Seedling emergence is affected by many factors, but optimal sand burial depth is required for germination and excavation [7].…”
Section: Introductionmentioning
confidence: 99%